2006
DOI: 10.1111/j.1445-2197.2006.03940.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Breast Cancer in a Small Peripheral New Zealand Hospital

Abstract: High rates of BCS are possible in peripheral hospitals. We postulate that intensive support and a visiting outpatient oncological service help empower patients to seek BCS if appropriate. A strong partnership between surgical, radiological and oncological services is also vital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…The overall BCT rate would have risen to 39% if radiotherapy facilities had been locally available, as 17 women would have changed their decision from mastectomy to BCT. This is still low, but more comparable with both national and international rates 4,8,9 . The distance to radiotherapy facilities (which is a surrogate for not only travel but time away from work, home and supporting family or friends) has been reported previously to be a potential factor in low BCT rates.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…The overall BCT rate would have risen to 39% if radiotherapy facilities had been locally available, as 17 women would have changed their decision from mastectomy to BCT. This is still low, but more comparable with both national and international rates 4,8,9 . The distance to radiotherapy facilities (which is a surrogate for not only travel but time away from work, home and supporting family or friends) has been reported previously to be a potential factor in low BCT rates.…”
Section: Discussionsupporting
confidence: 53%
“…This is still low, but more comparable with both national and international rates. 4,8,9 The distance to radiotherapy facilities (which is a surrogate for not only travel but time away from work, home and supporting family or friends) has been reported previously to be a potential factor in low BCT rates. Meden et al 10 found an association between distance to radiotherapy facilities and BCT with a 14.3% rate in rural areas (45 miles from radiotherapy facilities) compared with 41.7% in urban areas, n = 66.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the period under review however, only about one third of the patients with breast cancer received surgical treatment. This breast cancer surgery (BCS) rate was low compared to findings from a similar review in New Zealand where 58.6% of their patients over a 5 year period had BCS [7]. The reasons that possibly contributed to the low mastectomy rate in our patients include late presentation with inoperable local or metastatic tumours necessitating only palliative or terminal care, inability to pay out-of-pocket for treatment, and unwillingness to have mastectomy with consequent loss to follow up [9].…”
Section: Discussionmentioning
confidence: 88%